New records of Erotylidae (Coleoptera: Cucujoidea) for Colombia - GASCA-ÁLVAREZ, HÉCTOR JAIME (Revista Colombiana de Entomología, 2009)
Three species of pleasing fungus beetles of Erotylidae are recorded for the first time in Colombia, currently known from Peru, Brazil and Bolivia. Specimens are deposited in the insect collection of the Instituto de Ciencias Naturales (ICN) of the Universidad Nacional de Colombia.